THE UNIVERSAL INFORMATION TECHNOLOGY MODEL FOR DEPOSIT INSURANCE PAYOUTS - Žilinskas, Raimundas; Skyrius, Rimvydas (Ekonomika, 2014)
Abstract. The basic function of all deposit insurance schemes is to pay deposit insurance payouts to depositors promptly for the losses they otherwise would suffer in the event of an insured financial institution’s closure. As a result, depositors are relieved of both the recovery-rate and time risks of a liquidation process up to the insured level of their deposits. Deposit insurance payouts – including the speed and convenience – vary across countries and can affect public confidence in the deposit insurance scheme. Information technology support in the payout process is essential. However, one of the major problems in the insurance payout process is the lack of the proper information technology. This paper addresses the factors related to the payout process, discusses the advantages and disadvantages of various approaches, and makes recommendations on the establishment of a universal information technology model for a deposit insurer to accomplish the procedures of insurance payouts. Key words: deposit insurance, deposit insurance payouts, information technology support